Pengembangan Digital Book Dengan Aplikasi Kvisoft Flipbook Berbasis Problem Solving Untuk Meningkatkan Kemampuan Berpikir Tingkat Tinggi Siswa SMP - Wina Mariana Parinduri; Titin Rahmayanti Rambe (Mahesa Research Center, 2022)
Against the background of students' indifference to science lessons, student scores are still below the KKM, and students have not experienced different learning models or media. The aim of this research is to develop a science Digital Book learning media that uses Kvisoft Flipbook, based on solving problems about matter and its changes to explore the feasibility of Digital Book media obtained through expert validation and to find out the attractiveness through student responses. Types of research and development (Research and Development). Through research and development steps that are guided by the ADDIE model. The development stage involved six validators and four practitioners to assess the feasibility of the material and media. The implementation phase involved 70 students (25 students at AlMaksum Stabat Private Middle School, 25 students at Stabat 1 Public Middle School, and 20 students at Bintang Langkat Private Middle School). The validation results from material experts and media experts which were carried out in 2 stages obtained very feasible criteria with a percentage of 72.50% and media experts at 80.75%. The results obtained by material practitioners were 74.41% and media practitioners 84.71%. For students' responses to learning media in the form of problem solving-based digital books, the scores obtained were for Al Maksum Langkat Private Middle School at 80.74%, Stabat 1 Middle School at 81.22%, and Bintang Langkat Private Middle School at 80.74%.